2016
DOI: 10.1242/jcs.185629
|View full text |Cite
|
Sign up to set email alerts
|

EPAC1 activation by cAMP stabilizes CFTR at the membrane by promoting its interaction with NHERF1

Abstract: Cyclic AMP (cAMP) activates protein kinase A (PKA) but also the guanine nucleotide exchange factor 'exchange protein directly activated by cAMP' (EPAC1; also known as RAPGEF3). Although phosphorylation by PKA is known to regulate CFTR channel gatingthe protein defective in cystic fibrosis -the contribution of EPAC1 to CFTR regulation remains largely undefined. Here, we demonstrate that in human airway epithelial cells, cAMP signaling through EPAC1 promotes CFTR stabilization at the plasma membrane by attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…Nevertheless, a substantial amount of rescued CFTR remained stable, being present up to 8 h after cycloheximide administration. Perhaps our results obtained by co-administering C4 and C18 may be enhanced by including a "stabilizer" compound, such as those that promote the interaction between rescued CFTR mutant and Na + /H + exchanger regulatory factor 1 [43, 44]. However, co-administration of C4 and C18 did not rectify the trafficking, function, or stability of CFTR bearing G85E, leaving a continuing need for an effective treatment to rescue this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a substantial amount of rescued CFTR remained stable, being present up to 8 h after cycloheximide administration. Perhaps our results obtained by co-administering C4 and C18 may be enhanced by including a "stabilizer" compound, such as those that promote the interaction between rescued CFTR mutant and Na + /H + exchanger regulatory factor 1 [43, 44]. However, co-administration of C4 and C18 did not rectify the trafficking, function, or stability of CFTR bearing G85E, leaving a continuing need for an effective treatment to rescue this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Arora et al have shown that F508del can be stabilized at the cell surface with the use of VX-809 (a corrector molecule) by potentiation of its interaction with NHERF1 (3). More recently, it has been demonstrated that exchange protein directly activated by cAMP (EPAC1) interacts with NHERF1 through CFTR, and its activation is additive to F508del CFTR rescue with VX-809 (41). Taken together, the characterization of the 1417 EEN-KVR 1422 motif provides a new potential mechanism to manipulate the interaction between CFTR and NHERF1 to amplify the effect of small-molecule treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we uncovered a prominent long-range allosteric regulatory behavior in NHERF1: Upon Ezrin binding to NHERF1, the binding affinities of the PDZ domains of NHERF1 for target membrane proteins are dramatically increased, even though the PDZ domains are located more than 120 Å away from the Ezrin-binding site (6,20,21*). Thus, Ezrin allosterically modulates NHERF1 to assemble membrane protein complexes and to tether the assembled complexes to the cytoskeletal actin network, which modulates the cell surface targeting and intracellular trafficking of the assembled signaling complexes (22-24). …”
Section: Nherf1: a Paradigm Of Long-range Allosterymentioning
confidence: 99%